Handbook of Green Chemistry 2010
DOI: 10.1002/9783527628698.hgc028
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine‐Based Enzymes for Biotransformations

Abstract: Chiral and prochiral α‐oxyfunctionalized compounds, in particular carboxylic acids, aldehydes, ketones, alcohols, are indispensable building blocks for asymmetric synthesis. 2‐Hydroxy ketones encompassing a chiral and prochiral center are therefore versatile building blocks for organic synthesis, as they can be easily transformed into other functionalities, such as diols, epoxides, amino alcohols and diamines. The review describes the current state of the art concerning thiamine diphosphate‐dependent enzymes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 168 publications
0
14
0
Order By: Relevance
“…The same is true for the following pairs: acetone and TCM, DMSO and i Prop, THF and dioxane, and EtOAc and dioxane. It can be concluded that the less polar solvent can better accumulate in the non-polar S -pocket, since it is mainly built of hydrophobic amino acid side chains4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same is true for the following pairs: acetone and TCM, DMSO and i Prop, THF and dioxane, and EtOAc and dioxane. It can be concluded that the less polar solvent can better accumulate in the non-polar S -pocket, since it is mainly built of hydrophobic amino acid side chains4.…”
Section: Discussionmentioning
confidence: 99%
“…A well-known example is the carboligation of acetaldehyde and benzaldehyde catalyzed by pyruvate decarboxylases in fermenting yeasts yielding ( R )-1-hydroxy-1-phenylpropan-2-one (PAC), a precursor of ephedrine, with an ee >98% 3. In recent years, we have created a toolbox of ThDP-dependent enzymes including wild-type and engineered enzymes with varying selectivities to access a broad range of predominantly mixed aromatic and aliphatic chiral 2-hydroxy ketones 2f,4. In doing so, different organic cosolvents [e.g., dimethyl sulfoxide (DMSO),5 methyl tert -butyl ether (MTBE),6 2-methyltetrahydrofuran (MTHF)7] were used in order to increase the solubility of the aromatic compounds in the aqueous reaction system.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of all annotated sequences can be found in the ThDP‐dependent Enzyme Engineering Database (TEED, http://www.teed.uni-stuttgart.de) . Among these, enzymes catalysing the cleavage and formation of C–C bonds have been most intensively studied . Here, the potential to catalyse the formation of mixed carboligation products from a donor substrate and an acceptor substrate in a highly chemoselective and stereoselective manner is of special interest.…”
Section: Introductionmentioning
confidence: 99%
“…While the decarboxylation of 2-ketoacids [10] and the carboligation of two aldehydes to 2-hydroxy ketones are catalysed by most members of the ThDP-dependent decarboxylases [9], their substrate ranges are different. The well characterised PDC from Saccharomyces cerevisiae , BFD from Pseudomonas putida and BAL from Pseudomonas fluorescence accept a broad variety of substrates [7,11,12], while SEPHCHC-synthase (MenD) is limited to a small number of substrates [13,14]. Additional complexity of C-C bond formation results from the fact that a substrate might be either a donor, which is activated by addition to ThDP in the active site, or an acceptor, which reacts with the ThDP-bound donor, resulting in different products [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The well characterised PDC from Saccharomyces cerevisiae , BFD from Pseudomonas putida and BAL from Pseudomonas fluorescence accept a broad variety of substrates [7,11,12], while SEPHCHC-synthase (MenD) is limited to a small number of substrates [13,14]. Additional complexity of C-C bond formation results from the fact that a substrate might be either a donor, which is activated by addition to ThDP in the active site, or an acceptor, which reacts with the ThDP-bound donor, resulting in different products [7,11,12]. Reactions catalysed by members of the structural group of ThDP-dependent decarboxylases include decarboxylation of 2-keto acids, synthesis of various chiral 2-hydroxy ketones by asymmetric benzoin- [11,15] and cross-benzoin condensation [16,17], the racemic resolution of 2-hydroxy ketones via C-C bond cleavage [18], and Stetter-like reactions, e.g.…”
Section: Introductionmentioning
confidence: 99%